2022
DOI: 10.1139/as-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil content of Rhododendron tomentosum responds strongly to manipulation of ecosystem resources in Arctic Alaska

Abstract: The essential oils of the widely distributed boreal/Arctic dwarf shrub, Rhododendron tomentosum ssp. subarcticum (Harmaja) G.D. Wallace, have important ecological, cultural, medicinal, and commercial roles. To understand the relationship between resource limitation and essential oil content of this species we measured the amount and diversity of terpenes from shoots of plants exposed to a 14-year ecosystem resource manipulation experiment in Arctic Alaska. Treatments tested interactive effects of nitrogen (N) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In this last study, the composition of L. palustre ssp. decumbens also included some monoterpenes and monoterpenoids, including high proportions of cymene …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this last study, the composition of L. palustre ssp. decumbens also included some monoterpenes and monoterpenoids, including high proportions of cymene …”
Section: Resultsmentioning
confidence: 99%
“…subarcticum essential oil, has never been reported in L. palustre ssp. decumbens , , although we did find a low quantity of germacrone and myrcene in our essential oil extract. Another compound, p -cymene, is quite abundant, although not the most dominant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A unique study of warming, fertilization, and shading effects on the essential oil content of the evergreen shrub Rhododendron tomentosum showed that the highest oil concentrations were found in unmanipulated control plants and in those fertilized by a combination of N and P, whereas shading and addition of P resulted in the lowest concentrations. Warming also decreased the oil content by about 65% (Baldwin and Oberbauer 2022). The responses in essential oil content by R. tomentosum were also affected by the changes in the plant community after 14 years of treatments, especially the increase in shrub growth.…”
Section: Other Studies Of Individual Species and Species Traitsmentioning
confidence: 91%